(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
This study aims to conceptualize contemporary endowment companies from an Islamic economic perspective, ensuring their extend their benefits beyond an individual’s lifetime. The study also highlighted the precautions taken by Islamic law to protect waqfs, emphasizing the importance of accurately managing their expenditures and regulating activities to ensure benefits, prevent harm, and avoid corruption. The research included a review of the current regulations and rules governing the supervision of waqfs in the Kingdom of Saudi Arabia, and the judicial practices followed as far as accessible. The study encompassed various issues, benefits, and discussions that can be beneficial. The researcher recorded the key findings in the conclusion of the study.